ANALISIS PENGARUH HASIL RENDEMEN DAN WAKTU PADA ALAT PENGUPAS NANAS SEMI MEKANIS BERDASARKAN TIGA TINGKAT KEMATANGAN BUAH NANAS VARIETAS QUEEN - Pebriani Daulay, Diana; Melvi Viyona; Fatkhul Rohman; Ridos Sputra; Igef Rasinta; Latifa Aini; Anna Anggraini (JURAGAN - Jurnal Agroteknologi, 2025)
This study aims to analyze the effect of pineapple ripeness level on yield and peeling time using a semi-mechanical peeler. The experimental method used pineapple samples from three levels of ripeness: green, greenish yellow, and yellow. The results showed that the use of a peeler increased peeling efficiency compared to the manual method, with shorter peeling time and better yield in green and greenish yellow pineapples. This study aims to analyze the effect of pineapple ripeness level on yield and peeling time using a semi-mechanical peeler. The experimental method used pineapple samples from three levels of ripeness: green, greenish yellow, and yellow. The results showed that the use of a peeler increased peeling efficiency compared to the manual method, with shorter peeling time and better yield in green and greenish yellow pineapples. Although in yellow pineapples, the yield tends to be lower due to fruit damage during the peeling process. Although in yellow pineapples, the yield tends to be lower due to fruit damage during the peeling process.